PRINCIPLES OF SPIRITUAL CARE IN END-OF-LIFE CARE IN INDIA: A HISTORICAL-CULTURAL INVESTIGATION. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Inbadas, Hamilton; Seymour, Jane; Narayanasamy, Aru
Abstract : Background: Understanding the principles of spiritual care in end-of-life care pertaining to the Indian context is crucial for the development of an appropriate approach to spiritual care for Indian palliative care. The rich and diverse spiritual and cultural traditions around the care of the dying in the country provide useful resources for such a perception. Aims: This study seeks to examine the features of the care of the dying that were prevalent in the past in South India in order to understand the values and principles of spiritual care in the care of the dying in India. Methods: Taking a historical-cultural perspective, in-depth oral history interviews were conducted with thirty older adults belonging to different religions and none. Participants were recruited using purposive and snowballing sampling technique from Kanyakumari district, South India. Results: Several religious and cultural care practices that were customary in the care of the dying and beliefs about good death that prevailed over a couple of decades 40 years ago emerged from the data. 'Union with the divine', 'being at peace' and 'preserving dignity' were the three core principles that were found to be at the heart of these practices and beliefs. All these practices and beliefs were found to have meanings and values attached to them that relate to these core principles. Conclusions: Care practices around the care of the dying and beliefs about good death are clearly characterised by spiritual beliefs. Perspectives on the present Indian scenario suggest that the above said principles play a vital role in shaping the current understanding of death and ideas of good death. Considerable contextual changes in the Indian society have caused the breakdown of traditional patterns of intergenerational dissemination of these practices and their meanings making these core principles hard to achieve.